Lifetime Marijuana and Alcohol use, and Cognitive Dysfunction in People with Human Immunodeficiency virus Infection. Issue 1 (January 2018) - Lorkiewicz, Sara A.; Ventura, Alicia S.; Heeren, Timothy C.; Winter, Michael R.; Walley, Alexander Y.; Sullivan, Meg; Samet, Jeffrey H.; Saitz, Richard
Background: Substance use is common among people with human immunodeficiency virus (HIV) infection. Alcohol, marijuana, and HIV can have negative effects on cognition. Associations between current and lifetime marijuana and alcohol use and cognitive dysfunction in people with HIV infection were examined. Methods: Some 215 HIV-infected adults with Diagnostic and Statistical Manual of Mental Disorders Fourth Edition (DSM-IV) substance dependence or ever injection drug use were studied. In adjusted cross-sectional regression analyses associations were assessed between current marijuana use, current heavy alcohol use, lifetime marijuana use, lifetime alcohol use, duration of heavy alcohol use (the independent variables), and 3 measures of cognitive dysfunction (dependent variables): both the (i) memory and (ii) attention domains from the Montreal Cognitive Assessment (MoCA) and the (iii) 4-item cognitive function scale (CF4) from the Medical Outcomes Study HIV Health Survey (MOS-HIV). Analyses were adjusted for demographics, primary language, depressive symptoms, anxiety, comorbidities, antiretroviral therapy, hepatitis C virus (ever), duration of HIV infection (years), HIV-viral load (log copies/mL), CD4 cell count, lifetime and recent cocaine use, and recent illicit and prescribed opioid use. Results: Current marijuana use was significantly and negatively associated with the MOS-HIV CF4 score (adjusted mean difference = −0.40, P = .01). Current marijuana use was not significantly associated with either MoCA score. Lifetime marijuana use and current heavy and lifetime alcohol use and duration of heavy alcohol use were not associated with any measure of cognitive dysfunction. Conclusion: Current marijuana use was associated with one measure of cognitive dysfunction, but there was not a consistent pattern of association with lifetime marijuana use or alcohol use and measures of cognitive dysfunction. Understanding the mechanism by which marijuana, with and without alcohol, are associated with worse cognition warrants larger, longer studies with more precise and diverse measurements of cognitive function.